Nature-based preschool gardens for thermal condition regulation: Implications for climate-sensitive policy and planning - Lupa, Piotr; Zwierzchowska, Iwona (Quaestiones Geographicae, 2025)
Cities are places with concentrations of people and the effects of their activities, which are particularly exposed to the impacts of climate change. In this respect, one of the challenges for planners and decision-makers is urban heat mitigation regarding the higher intensity of heat islands and heat waves. Shaping urban tissue is fundamental in ensuring thermal comfort for city dwellers. Particular attention should be paid to children as they are more vulnerable to thermal stress. Hence, the study aims to enhance climate-sensitive urban planning and policy by providing evidence on the impact of green infrastructure (GI) and small-scale nature-based solutions (NBSs) such as preschool gardens (PGs) in urban heat mitigation in Poznań, Poland. In addition to recognising the thermal conditions of PGs, we investigated their thermal impact on the surrounding areas. We also analysed preschoolers’ exposure to urban heat during their stay in PGs. The study employed Geographic Information System (GIS) and remote sensing data from Landsat 8 to generate the normalised difference vegetation index (NDVI) and surface temperature rasters. The results reveal that the thermal impact of PGs depends on their size, NDVI and the tree canopy cover (TCC) of both PGs and their surroundings. PGs are valuable areas that regulate thermal conditions in the city. We recommend optimising PGs into more nature-oriented spaces (NDVI > 0.3) that might play the additional role of site-scale cooling shelters. The universal methodology developed and adopted in the study allows for scaling the research to other cities in the temperate climate zone.